2008
DOI: 10.1518/001872008x250728
|View full text |Cite
|
Sign up to set email alerts
|

Postural Instability and Motion Sickness in a Virtual Moving Room

Abstract: Objective-We examined motion sickness in an oscillating virtual environment presented via a video projector system.Background-Visible oscillation of the physical environment is known to induce both postural instability and motion sickness, but it cannot be assumed that the same phenomena will occur in a virtual simulation of such motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 20 publications
10
58
3
3
Order By: Relevance
“…This result resembles similar findings from studies of video games [8], virtual environments [6], and vehicle simulators [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result resembles similar findings from studies of video games [8], virtual environments [6], and vehicle simulators [7].…”
Section: Discussionsupporting
confidence: 88%
“…This effect has been observed in laboratory devices, virtual environments, flight simulators, and console video games [5][6][7][8]. Interestingly, in console video games postural instability and motion sickness are common among individuals who control the game (i.e., players), and occur in games that depict ambulation (i.e., walking or running) rather than vehicular travel [8].…”
Section: Introductionmentioning
confidence: 93%
“…Earlier studies reported similar increases on postural sway effects of 2D and 3D motion stimuli, however, in separate studies ( [8][9][10][11]42] versus [12], respectively). With this study we were able to compare postural sway caused by viewing 2D and 3D motion stimuli in one single study, and observed that exposure to 3D motion stimuli did not cause more postural sway compared to viewing 2D.…”
Section: Discussionmentioning
confidence: 59%
“…In addition to VIMS symptoms, viewing motion stimuli can also affect postural control, defined as ''the act of maintaining, achieving or restoring a state of balance during any posture or activity" [7]. In particular it has been shown that postural sway increases due to viewing 2D [8][9][10][11] and 3D motion stimuli [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation